Biochanin A Promotes Osteogenic but Inhibits Adipogenic Differentiation: Evidence with Primary Adipose-Derived Stem Cells. (16th June 2013) - Su, Shu-Jem; Yeh, Yao-Tsung; Su, Shu-Hui; Chang, Kee-Lung; Shyu, Huey-Wen; Chen, Kuan-Ming; Yeh, Hua
Abstract : Biochanin A has promising effects on bone formation in vivo, although the underlying mechanism remains unclear yet. This study therefore aimed to investigate whether biochanin A regulates osteogenic and adipogenic differentiation using primary adipose-derived stem cells. The effects of biochanin A (at a physiologically relevant concentration of 0.1–1 μ M) were assessed in vitro using various approaches, including Oil red O staining, Nile red staining, alizarin red S staining, alkaline phosphatase (ALP) activity, flow cytometry, RT-PCR, and western blotting. The results showed that biochanin A significantly suppressed adipocyte differentiation, as demonstrated by the inhibition of cytoplasmic lipid droplet accumulation, along with the inhibition of peroxisome proliferator-activated receptor gamma (PPAR γ ), lipoprotein lipase (LPL), and leptin and osteopontin (OPN) mRNA expression, in a dose-dependent manner. On the other hand, treatment of cells with 0.3 μ M biochanin A increased the mineralization and ALP activity, and stimulated the expression of the osteogenic marker genes ALP and osteocalcin (OCN). Furthermore, biochanin A induced the expression of runt-related transcription factor 2 (Runx2), osteoprotegerin (OPG), and Ras homolog gene family, member A (RhoA) proteins. These observations suggest that biochanin A prevents adipogenesis, enhances osteoblast differentiation in mesenchymal stem cells, and has beneficial regulatory effects in bone formation.